Analysis of Social Criticism on Power Relations, Ideology, and Societal Oppression in the Arabic Film Masyithah - Lathifa, Rahma Maulidya (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research aims to analyze social criticism, ideology, and superstructure in the film Masyithah. The film portrays power relations and forms of oppression between the ruling class and the oppressed society within the film’s narrative. This research uses a social criticism approach with a descriptive qualitative method. The data collection technique is carried out through the analysis of scenes, dialogues, and characters in the film Masyithah to identify the forms of social criticism contained in it. The results of the research show that the film represents the dominance of power through the character of Pharaoh as the ruling class who imposes ideology on society, while the character of Masyithah is depicted as the oppressed party who experiences pressure, threats, and torture for maintaining her faith. The oppression carried out by Pharaoh reflects the dominance of power, while Masyithah’s resistance shows critical awareness of injustice and becomes a symbol of the struggle of the oppressed class in defending the truth.